1999
DOI: 10.1002/(sici)1521-3773(19991203)38:23<3530::aid-anie3530>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

A Stereospecific, Intermolecular Biaryl-Coupling Approach to Korupensamine A En Route to the Michellamines

Abstract: By what means and how well can axial chirality be controlled in an intermolecular Suzuki biaryl cross-coupling reaction? The directionality of reductive elimination [Eq. (1)] is completely controlled by using a strategically positioned internal ligand L to afford a single biaryl atropisomer corresponding to the korupensamine A skeleton. TIPS=iPr(3)Si, Ts=H(3)CC(6)H(4)SO(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 5 publications
1
30
0
Order By: Relevance
“…Lipshutz and Keith synthesised their functionalised heterocyclic portion by allowing the Grignard reagent derived from chloride 1.12 to react with commercially available (S)-TBSglycidol (1.16) to give alcohol 14 Nitrogen functionality was introduced by Mitsunobu inversion with phthalimide, followed by deprotection to give chiral amine which was Chapter 1 Introduction 9 readily converted into dihydroisoquinoline 1.19 using similar chemistry to that described earlier in this section (Scheme 1.4). A useful feature of this sequence is the ability to retain a labile protecting group, such as a TBS (t-butyldimethylsilyl) ether, throughout the synthesis.…”
Section: Electrophilessupporting
confidence: 82%
“…Lipshutz and Keith synthesised their functionalised heterocyclic portion by allowing the Grignard reagent derived from chloride 1.12 to react with commercially available (S)-TBSglycidol (1.16) to give alcohol 14 Nitrogen functionality was introduced by Mitsunobu inversion with phthalimide, followed by deprotection to give chiral amine which was Chapter 1 Introduction 9 readily converted into dihydroisoquinoline 1.19 using similar chemistry to that described earlier in this section (Scheme 1.4). A useful feature of this sequence is the ability to retain a labile protecting group, such as a TBS (t-butyldimethylsilyl) ether, throughout the synthesis.…”
Section: Electrophilessupporting
confidence: 82%
“…This group is easily attached to the substrate through esterification of an appropriate alcohol function. The multifunctional character of this group is notable; it can act as an efficient directing [52,53], and a palladium-catalyzed atropselective biaryl coupling [54] have been described. Thus, enoates 127-131 were prepared efficiently by means of a combination of an o-DPPB-directed stereoselective hydroformylation and a Horner-WadsworthEmmons (HWE) olefination (Scheme 6.26).…”
Section: Directed Conjugate Addition Reactionsmentioning
confidence: 99%
“…Uemura,52–54 Nelson,55 Colobert56 and Lipshutz57 demonstrated that axially chiral biaryl products are formed in high yields and excellent selectivities in Pd-catalyzed Suzuki-Miyaura reactions with aryl halides bearing chiral auxiliaries. Later Nicolaou employed chiral phosphines to modulate the selectivity of a diastereoselective Suzuki-Miyaura reaction used in the synthesis of vancomycin 9…”
Section: Introductionmentioning
confidence: 99%